Distributed Coherent Aperture Radar Enabled by Microwave Photonics - LI Shangyuan; XIAO Xuedi; ZHENG Xiaoping (Leida xuebao, 2019)
Distributed Coherent Aperture Radar (DCAR) utilizes multiple separated antenna apertures to emit signals in the same space area, realizing spatial coherent synthesis of electro-magnetic waves. Such a flexible radar system has advantages such as higher resolution, greater radar power, and lower cost. Combined with microwave photonic technologies, which have merits in wideband signal generation, transmission and procession, the DCAR has a comprehensive and better performance. This paper introduces a microwave photonics-based high-resolution distributed coherent aperture radar that was proposed by researchers of Tsinghua University. Taking advantages of microwave photonic technology, a group of wideband orthogonal phase-coded linear frequency modulation waves is generated in the coherence-on-receive mode, with the frequency ranging from 8.5 GHz to 11.5 GHz, all with phase coding under a bit rate of 0.5 Gbps. The orthogonality of the signals is nearly 30 dB, and the range resolution is better than 0.05 m. While in the full coherence mode, the transmitted waveforms can be flexibly switched to the wideband coherent linear frequency modulation waves, and the full coherent synthesis can be realized. The waveforms generated by the proposed system can meet the waveform requirements of the DCAR in different operation modes. In the experiment, full coherence is achieved with two sets of radars, resulting a signal- to-noise ratio gain of 8.3 dB.